Iron Deficiency Anemia as The Only Manifestation of Colon Cancer in Male Patient: A Case Report - Wulyo Rajabto; Pandu Tridana Sakti; Andi Putra Kevinsyah (The Indonesian Society for Digestive Endoscopy, 2020)
Iron deficiency anemia can be the first manifestation of colon cancer. However, iron deficiency anemia is also common in other benign conditions, which may cause a longer delay for referral decisions to get a definitive diagnosis. This is a case of 40-year-old male patient who had only iron deficiency anemia as a manifestation of colon cancer. Colonoscopy revealed intraluminal mass in transverse colon. After resection of the tumor, histopathology showed well-differentiated mucinous adenocarcinoma, invasion of sub-serous, and one node positive (pT3pN1pM0). After resection, we administered XELOX as adjuvant chemotherapy every 3 weeks for 8 cycles.